GNSS ambiguity resolution with ratio and fixed failure ratio tests for long baseline network RTK under ionospheric activity - Silva, C. M. [UNESP]; Setti Júnior, P. T. [UNESP]; Alves, D. B.M. [UNESP]; Souza, E. M. (Elsevier, 2020)
To perform network RTK positioning, a user must receive and apply the information generated from a network. Corrections are generated for the user to consider the atmospheric delays (ionosphere and troposphere) between ther location and the network stations. In order to generate reliable corrections and send them to users, one must resolve the ambiguities in the processing step of the network stations. Ambiguities are the number of integer cycles of the carrier phase in the first data collection epoch and are introduced as parameters to be estimated in the processing. Thus, the ambiguity resolution process becomes a prerequisite for obtaining high accuracy in network RTK positioning. This process can be divided into two steps: estimation and validation. The estimation step aims to obtain the integer values of ambiguities and in the validation step it is inferred if the estimated integer value may or may not be accepted. In this work, the LAMBDA (Least squares AMBiguity Decorrelation Adjustment) method was used to obtain the integer ambiguity estimate and for the validation the Ratio and FF-RT (Fixed Failure Ratio Test) tests were used. The objective of this work was to investigate the performance of the ambiguities validation tests for long baselines. The results showed that the FF-RT test presented the highest fixed ambiguity percentages when compared to the Ratio test in all analyzed periods. Thus, for long baselines positioning, in periods of either weak or strong ionospheric activity, the use of the FF-RT test will cause a greater number of fixed ambiguities to be used in the process of generating the corrections for the user.
Keywords: Ambiguity; FF-RT; GNSS; Long baseline; Ratio; Validation